Objective assessment of shared plate eating using a wearable camera in urban and rural households in Ghana - Domfe, Christabel A.; McCrory, Megan A.; Sazonov, Edward; Ghosh, Tonmoy; Raju, Viprav; Frost, Gary; Steiner-Asiedu, Matilda; Sun, Mingui; Jia, Wenyan; Baranowski, Tom; Lo, Benny; Anderson, Alex K. (Frontiers in Nutrition, 2024)
Background Shared plate eating (SPE), defined as two or more individuals eating directly from the same plate or bowl, is a common household food consumption practice in many Low- and Middle-Income Countries (LMICs). Examination of household engagement in SPE remains largely unexplored, highlighting a gap in research when interpreting dietary information obtained from these settings. The dearth of research into SPE can be attributed to the inherent limitations of traditional dietary assessment methods which constrain their usability in settings where SPE is common. Objective In this expository narrative, we describe what SPE is when it is practiced in an LMIC such as Ghana; and also compare the frequency of SPE versus individual plate eating (IPE) by different household members in rural and urban households using a wearable camera (Automatic Ingestion Monitor version 2: AIM-2). Methods Purposive convenience sampling was employed to recruit and enroll 30 households each from an urban and a rural community (n = 60 households) in Ghana. The AIM-2 was worn on eyeglass frames for 3 days by selected household members. The AIM-2, when worn, automatically collects images to capture food consumption in participants’ environments, thus enabling passive capture of household SPE dynamics. Results A higher percentage of SPE occasions was observed for rural (96.7%) compared to urban (36.7%) households (p < 0.001). Common SPE dynamics included only adults sharing, adults and children sharing, only children sharing, and non-household member participation in SPE. Conclusion The wearable camera captured eating dynamics within households that would have likely been missed or altered by traditional dietary assessment methods. Obtaining reliable and accurate data is crucial for assessing dietary intake in settings where SPE is a norm.